The Strengthening Family Communication Bond through WhatsApp Media Group in Timor Leste - Miqueias da Conceicao (Lingkar Studi Komunikasi (LISKI), 2022)
The presence of social media in this digital era especially WhatsApp messenger is considered to be able to facilitate the communication process for everyone. The use of WhatsApp is not only intended for interpersonal communication. However, WhatsApp also offers a feature where users can communicate in a group or what is also called the WhatsApp group feature. Today, WhatsApp groups have become a media of communication that is commonly used among families, especially in Dili, Timor Leste. The presence of the WhatsApp Family Group has also helped the family in the way of communicating with each other. This research is conducted to identify how the WhatsApp Family Group strengthens the communication family bond over families in Dili, Timor Leste. This research was utilizing the new media theory and qualitative approach with the descriptive method through the interview, observation, and documentation study. The results of this study pointed that the WhatsApp group has strengthened the family communication bond and also WhatsApp group has become media of communication, media information and media of entertainment for family utilized WhatsApp group in Dili, Timor-Leste. Keywords: Family Communication, New Media, Family Bond, WhatsApp Family Group